1982
DOI: 10.1103/physreva.26.2281
|View full text |Cite
|
Sign up to set email alerts
|

Resonantly enhanced, three-photon ionization of Xe: Optically pumped rare-gas laser

Abstract: Three-photon ionization of xenon, resonantly enhanced by the Xe 6p [1/2]c state at g0 119 cm ', is observed when a xenon atom simultaneously absorbs one ArF (51733-cm ') and two XeF (28482-cm ) photons. For ArF and XeF laser intensities in the 1 -100-MWcm range, the peak electron density is more than an order-of-magnitude larger than that obtainable by the nonresonant, two-photon ionization of Xe by ArF. The spontaneous radiative lifetime of the 6p[1/2]c level and the rate constant for quenching of the state b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…In addition to the amplified stimulated emission, the single-color, two-photon excitation of the Xe͑6p, 6pЈ and 7p͒ states in low pressure of Xe can produce other nonlinear Raman scattering processes, and these also may have practical importance. Three-photon resonance ionization 36 and collisional ionization processes also can occur and care must be exercised in choosing experimental conditions to control the degree of ionization.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the amplified stimulated emission, the single-color, two-photon excitation of the Xe͑6p, 6pЈ and 7p͒ states in low pressure of Xe can produce other nonlinear Raman scattering processes, and these also may have practical importance. Three-photon resonance ionization 36 and collisional ionization processes also can occur and care must be exercised in choosing experimental conditions to control the degree of ionization.…”
Section: Discussionmentioning
confidence: 99%
“…The first observation of the SE effect in Xe was reported in Ref. 2. Irradiating a cell containing Xe gas at a pressure of 20 Torr with ArF λ = 193 nm and XeF λ = 351 nm lasers, the authors observed stimulated 6p [1/2] 0 → 6s[3/2] 1 emission at λ = 828.0 nm (the combined energy of the λ = 193 and 351 nm photons matches the 6p[1/2] 0 energy).…”
Section: And the References Cited Therein)mentioning
confidence: 99%
“…In Ref. 2 Xe gas was excited laterally. The length of the volume containing excited Xe atoms was determined by the length of the rectangular laser beams (2.9 cm).…”
Section: And the References Cited Therein)mentioning
confidence: 99%
See 1 more Smart Citation